When normality fails - Richard Mohr (Oñati Socio-Legal Series)
Shocks from disasters challenge the normality of everyday life. Emotional and political reactions include anxiety and blame, but these must come together with knowledge through shared discourse to formulate responses, often immediate. The study draws on a phenomenological analysis of personal experience and discursive reactions to fires and the pandemic. It is informed by ethical and social approaches to epistemology and discourse, drawing on sociology of knowledge and studies of rhetoric. From this it is concluded that facts are agreed elements for debate, as in the legal tradition, rather than guarantees of certainty. Knowledge relevant to disaster discourse arises through shared experience and robust communicative institutions, from the local to the scientific, and including the wisdom of First Nations. Disasters are uncanny because they defy everyday know-how. In disrupting the relationship of people to their milieu, they require a new accommodation among and between human and non-human actors.